Part 2: Effect of training surface on acute physiological responses after interval training - Binnie, M. J.; Dawson, B.; Pinnington, H.; Landers, G.; Peeling, P. (The Journal of Strength and Conditioning Research, 2013)
This study compared the effect of sand and grass training surfaces during a sport-specific conditioning session in well-trained team sport athletes (n = 10). The participants initially completed a preliminary testing session to gather baseline (BASE) performance data for vertical jump, repeated sprint ability, and 3-km running time trial. Three days subsequent to BASE, all the athletes completed the first sport-specific conditioning session, which was followed by a repeat of the BASE performance tests the following day (24 hours postexercise). Seven days later, the same training session was completed on the opposing surface and was again followed 24 hours later by the BASE performance tests. During each session, blood lactate, ratings of perceived exertion (RPE), and heart rate (HR) were recorded, with player movement patterns also monitored via global positioning system units. Additionally, venous blood was collected preexercise, postexercise, and 24 hours postexercise, and analyzed for serum concentrations of Myoglobin, Haptoglobin, and C-Reactive Protein. Results showed significantly higher HR and RPE responses on SAND (p > 0.05), despite significantly lower distance and velocity outputs for the training session (p > 0.05). There were no differences in 24 hours postexercise performance (p > 0.05), and blood markers of muscle damage, inflammation and hemolysis were also similar between the surfaces (p > 0.05). These results suggest that performing a sport-specific conditioning session on a sand (vs. grass) surface can result in a greater physiological response, without any additional decrement to next-day performance.